2014
DOI: 10.1155/2014/729195
|View full text |Cite
|
Sign up to set email alerts
|

Da‐Bu‐Yin‐Wan and Qian‐Zheng‐San to Neuroprotect the Mouse Model of Parkinson’s Disease

Abstract: Da-Bu-Yin-Wan (DBYW) and Qian-Zheng-San (QZS), two classic traditional Chinese medicinal formulas, were clinically employed to treat Parkinson's disease (PD). Our previous studies demonstrated neuroprotective effects of them on mitochondrial function in PD mice induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). The purpose of this research was to investigate their possible mechanisms in the light of mitochondrial ATP-sensitive potassium (mitoKATP) channels. The neuroprotective effect of DBYW and Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(58 reference statements)
2
5
0
Order By: Relevance
“…All the above information provides some basis for the selection of Chinese formulas in our research (Gu and Yuan, 2013). The previous study of our research group also confirmed that DBYW and QZS could reduce MPTP-induced damage to the nucleus membranes and mitochondria in the substantia nigra of PD mice (Zhang et al, 2013; Gong et al, 2014), and we further discovered at the cellular level that DBYW and QZS could increase the length of mitochondria and reduce mitochondrial fragments in SH-SY5Y cells processed with MPP + (Ma et al, 2015). In addition, modern studies found that some active ingredients in DBYW and QZS could protect the activity of substantia nigra DA neurons.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…All the above information provides some basis for the selection of Chinese formulas in our research (Gu and Yuan, 2013). The previous study of our research group also confirmed that DBYW and QZS could reduce MPTP-induced damage to the nucleus membranes and mitochondria in the substantia nigra of PD mice (Zhang et al, 2013; Gong et al, 2014), and we further discovered at the cellular level that DBYW and QZS could increase the length of mitochondria and reduce mitochondrial fragments in SH-SY5Y cells processed with MPP + (Ma et al, 2015). In addition, modern studies found that some active ingredients in DBYW and QZS could protect the activity of substantia nigra DA neurons.…”
Section: Discussionsupporting
confidence: 74%
“…The Chinese medicinals in the two formulas are commonly used for the treatment of PD (Gu and Yuan, 2013; Lu et al, 2016). Our previous research confirmed that DBYW and QZS could regulate brain mitochondrial genes in PD animals and improve mitochondrial morphological structure of tannin neurons (Zhang et al, 2013; Gong et al, 2014). In order to further explore the mechanism of the effects of Chinese herbal compound in preventing and treating PD in mitochondria, the MPP + - induced PD cell model was selected to observe the molecular mechanisms of the effects of DBYW and QZS on mitochondria in PD cell model.…”
Section: Introductionsupporting
confidence: 72%
“…The mixtures were centrifuged at 12,000 g for 30 s. The luminescence in the supernatant was recorded according to ATP-dependent luciferase activity, using the microplate reader Safire2 (Tecan, Männedorf, Switzerland). The bioluminescence value was normalized by the protein concentration that measured using bicinchoninic acid kit ( Gong et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, DBYW lessens the DNA damage of mitochondria, and increases the mitochondrial subunit NADH dehydrogenase 1 expression ( Zhang et al, 2013 ). Moreover, DBYW up-regulates cellular adenosine 5′-triphosphate (ATP) content in the midbrain, and decreases the expression of ATP-sensitive potassium channel subunit ( Gong et al, 2014 ). Additionally, DBYW could reduce the mitochondrial fragmentation induced by the PD-related mitochondrial toxin (1-methyl-4-phenylpyridinium) in human derived neuroblastoma cell line ( Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formula of Da‐Bu‐Yin‐Wan was originated from Dan Xi Xin Fa, and it was written by Zhu Danxi of Yuan Dynasty in China. Zhu Danxi was the most famous physician in China Yuan Dynasty (A.D. 1206–1368) . Zhu Danxi is known as the founder of “nourishing yin school.” He advocated that “yang is often enough but yin is deficient” and thus he created the theory of yin deficiency pathogenesis and often used prescription with the effect of nourishing yin and purging fire .…”
Section: Introductionmentioning
confidence: 99%